Police oversight in practice: the Special Investigations Unit and civilian police oversight in Ontario, Canada - Puddister, Kate (Policing and society, 2024)
The Special Investigations Unit (SIU) of Ontario is a civilian police oversight agency responsible for investigating serious incidents involving police officers and civilians, with the power to charge police officers with criminal offences. Created in 1990, the SIU is considered a pioneer in civilian-led oversight, however, little is known about how the SIU conducts investigations, the complainants in these investigations, and the routine work of this oversight agency. This article examines a variety of indicators to document the work and activity of the SIU, illustrating important aspects of the agency’s performance in the process. Important trends regarding the nature of police misconduct, violence, and use of lethal force are analysed. Our study uncovers previously unknown trends regarding complainants in SIU investigations, including the prevalence of certain characteristics like known mental health disabilities and the relationship between the substantiation of complaints by the SIU and the criminal activity of the complainant. This study empirically documents the nature of police cooperation with oversight. By analysing different indicators of agency performance and work, this study makes an important contribution to the study of police oversight in general, and the findings hold value for understanding police use of force, the nature of police criminality and misconduct, and the functioning of civilian police oversight in practice.